Die Wirklichkeit der Freiheit begreifen Hegels Begriff von Sittlichkeit als Voraussetzung der Sittlichkeitskonzeption Kants - Krijnen, Christian (Folia Philosophica, 2018)
The relationship between Hegel’s conception of Sittlichkeit and Kant’s moral philosophy is much-discussed, highly controversial and accompanied by many misunderstandings. Relating it to Kant’s philosophy, this article shows that and how Hegel’s elaborations on Sittlichkeit can be understood as an attempt to comprehend the actuality of freedom in the human world. By contrast, the formalism of a Kantian approach of moral philosophy hinders it willy-nilly to comprehend the actuality, hence, the ‘fact’ of freedom properly. Hegel’s Sittlichkeit is a conception of the facticity of freedom. Kant’s conception of Sittlichkeit presupposes such a conception.